People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2004 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that after a period of prolonged weakness in economic activity, persistent deflation and rising fiscal deficits, the macroeconomic outlook for Hong Kong Special Administrative Region has improved significantly since mid-2003. The recovery has gained significant momentum and become broad-based in 2004. The consolidated fiscal deficit for FY2004/05 is now projected at about 1 3/4 percent of GDP, compared with the budget target of about 5 percent of GDP. The improvement relative to the budget is on account of buoyant revenue performance and continued expenditure restraint.